Analisis Permasalahan Pelaku Usaha dalam Proses Pemenuhan Komitmen Registrasi Pangan Olahan Risiko Menengah Rendah - Ira Novianty Lestari; Raden Bayu Indradi; Nurul Wahyu Wadarsih (Asosiasi Riset Ilmu Kesehatan Indonesia, 2024)
Before processed food is marketed in Indonesia, business actors must register the food to obtain a distribution permit. For medium to low risk processed food, a distribution permit must be obtained by obtaining a Business Activity Support Business Permit (PB-UMKU) with a Certificate of Fulfillment of Processed Food Commitments. This article will discuss the difficulties faced by industry players in this process and explain the fulfillment of registration commitments for low-medium processed food. This research method is a literature search using a legislative approach in processing processed food registration, and to collect field research questions, a survey of business actors was carried out during the technical guidance activity